Evaluation of predictive and prognostic importance of lung immune prognostic index in locally advanced rectal cancer patients treated with neoadjuvant chemoradiotherapy - ALKIŞ, HİLAL; ADLI, MUSTAFA (My University, 2023)
Objective: The systemic inflammatory response (SIR) is known as an important factor associated with tumorigenesis and tumor progression, and can be reflected by inflammatory markers. One of the markers that reflect this is the lung immune prognostic index (LIPI). It is based on a derived neutrophil-to-lymphocyte ratio (dNLR) and lactate dehydrogenase (LDH) level. We aimed to investigate the significance of LIPI in locally advanced rectal cancer (LARC) patients treated with neoadjuvant chemoradiotherapy (NACRT). Methods: In this retrospective study, we stratified the patients according to LIPI score as good LIPI and intermediate (int)/poor LIPI. According to pathological response to NACRT, we divided the patients into two groups as those with complete response (CR) or near-CR, and those with partial response (PR) or poor/no response. We classified CR and near-CR as good response. We evaluated the predictive and prognostic significance of LIPI for NACRT response, disease-free survival (DFS), and overall survival (OS) by univariate and multivariate analyses. Results: We included 137 patients in the results, with 72 (52.6%) having good LIPI and 65 (47.4%) having int/poor LIPI. The median follow-up period was 44.7 months (range: 10-105 months). Thirteen patients (18.0%) in the good LIPI group and 22 patients (34.0%) in the int/poor LIPI group achieved good response. In multivariate analysis, we found only the LIPI score as an independent risk factor (hazard ratio (HR): 2.4, p = 0.04) for NACRT response. Median DFS was 89.2 months (95% CI: 11.4-167.0) in the int/poor LIPI group; however, the DFS of all study populations and patients in the good LIPI group did not reach the median value. In multivariate analysis for DFS, we identified abdominoperineal resection (APR) (HR: 2.21, p = 0.02), presence of tumor deposit (HR: 2.96, p = 0.003), and int/poor LIPI score (HR: 2.07, p = 0.02) as separate risk variables. OS of all study populations and the patients in the LIPI groups did not reach the median value. In multivariate analysis for OS, we identified APR (HR: 2.74, p = 0.02), surgical margin positivity (HR: 12.94, p < 0.001), and adjuvant CT (HR: 0.20, p = 0.002) as separate risk variables for OS. Conclusion: This is the first study investigating the predictive and prognostic significance of LIPI in LARC patients treated with NACRT. The results revealed that int/poor LIPI was associated with a higher rate of good response but shorter DFS compared to good LIPI. The baseline LIPI score serves as an easily accessible and useful prognostic index, and it has significant potential for making appropriate treatment decisions in LARC.
Keywords: rectal cancer; prognosis; pathological response; neoadjuvant chemoradiotherapy; lung immune prognostic index